The relative contributions of functional diversity and functional identity to ecosystem function in water‐limited environments. (5th May 2019) - Dovrat, Guy; Meron, Ehud; Shachak, Moshe; Golodets, Carly; Osem, Yagil
Abstract: Questions: Two central pathways have been proposed to dictate the relationship between community structure and ecosystem function: the "diversity effect" — trait variation allowing complementary resource use, and the "mass ratio effect" — ecosystem function determined overwhelmingly by the functional traits of the dominant species which shape the "functional identity", i.e., community‐weighted mean trait values. However, the distinct effect of each pathway on ecosystem function is difficult to determine as they are complementary and shaped by environmental heterogeneity. We examined the distinct effects of functional diversity (FD) and identity (FI) on water consumption and use efficiency (WUE), vegetative and reproductive biomass production and reorganization capacity under variable water availability. Methods: Eight semiarid annual plant species, varying in natural size range, were grown in different assemblages representing various levels of FD and FI. Assemblages were based on species potential growth rate (PGR) and grown under two water availability levels. We measured total biomass, seed biomass, root to shoot ratio and water consumption. Results: FD had a distinct positive effect on water consumption, total biomass and seed production but not on WUE. Mean PGR (FI) had a distinct positive effect on water consumption and total biomass production, but a negative effect on WUE and seed production. FD and FI had no clear effects on reorganization capacity or stability in total biomass production in response to decreased water availability. Conclusions: We present the discrete contributions of FD and FI to ecosystem function. The positive effect of FD on biomass production reflects better exploitation of the growing space and reduced competition through greater size diversity, emphasizing the importance of interplant interactions and differentiation for enhancing ecosystem function. The positive effect of FI on biomass production reflects the higher performance of high PGR species, albeit at the expense of WUE and seed production resulting from higher competition. Abstract : We present the discrete contributions of functional diversity and functional identity to annual plant community productivity. Functional diversity increases biomass production via better exploitation of the growing space and reduced competitive equality through greater size diversity. Functional identity increases biomass production via higher performance of high growth rate species, but WUE and seed production decrease due to increased competition.